1996
DOI: 10.1002/(sici)1098-2744(199612)17:4<235::aid-mc7>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein kinase C and proto-oncogene expression by crocetin in NIH/3T3 cells

Abstract: Crocetin, a carotenoid isolated from the seeds of Gardenia jasminoides, was found to be a potent inhibitor of tumor promotion induced by 12-O-tetradecanoylphorbol-13-acetate (TPA) in mouse skin. When mouse fibroblast NIH/3T3 cells were treated with TPA alone, protein kinase C (PKC) translocated from the cytosolic fraction to the particulate fraction. Pretreatment with 60 and 120 microM crocetin for 15 min inhibited the TPA-induced PKC activity in the particulate fraction by 50% and 66%, respectively, but did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The results showed that crocetin inhibits c‐Jun, c‐Fos, and c‐Myc gene expression in NIH/3T3 cells. Crocetin also inhibits H 2 O 2 , myeloperoxidase and PKC activity in TPA‐induced skin tumor in mice, but no effect was observed on PKC protein level (Wang, Lee, Chang, & Lin, ; Wang et al, ). It was shown that oral administration of SE (200 mg/kg) inhibits the growth of ascite tumors derived from S‐180, EAC, and DLA in a dose‐dependent manner, and significantly elevated (2‐ to 3‐fold) life spans of treated tumor‐bearing Swiss albino mice.…”
Section: Anticancer Activity Of Crocetinmentioning
confidence: 99%
“…The results showed that crocetin inhibits c‐Jun, c‐Fos, and c‐Myc gene expression in NIH/3T3 cells. Crocetin also inhibits H 2 O 2 , myeloperoxidase and PKC activity in TPA‐induced skin tumor in mice, but no effect was observed on PKC protein level (Wang, Lee, Chang, & Lin, ; Wang et al, ). It was shown that oral administration of SE (200 mg/kg) inhibits the growth of ascite tumors derived from S‐180, EAC, and DLA in a dose‐dependent manner, and significantly elevated (2‐ to 3‐fold) life spans of treated tumor‐bearing Swiss albino mice.…”
Section: Anticancer Activity Of Crocetinmentioning
confidence: 99%
“…The authors suggest that crocetin suppressed TPAinduced skin carcinogenesis, probably through its antioxidant property, leading in turn to a reduction in TPA-induced expressions of oncoproteins [52]. In vitro, crocetin significantly inhibits TPA-induced translocation of protein kinase C (PKC) from the cytosolic fraction to the particulate fraction, phosphorylation of cellular proteins, and c-jun and cfos gene expression in mouse fibroblast NIH/3T3 cells [53]. In addition, local application of crocetin markedly restricts TPA-induced promotion of skin tumors, and hyperplasia and edema initiated in mouse ear with benzo[a]pyrene (BP).…”
Section: Hemorrhagic Shockmentioning
confidence: 99%
“…Liu et al (2020)CrocinMale Sprague Dawley rats Reduction of experimentally-induced hepatocellular carcinoma through modulating the oxidative/apoptotic pathway. Crocin-induced hepatic expression of Nrf2 improved downstream modifications in KEAP-1 and HO-1 signalling pathway.Elsherbiny et alCrocin delayed papilloma's formation in mice .Konoshima et al (1998)Crocetin Mice fibroblast NIH/3T3 cells 120 and 60 µM crocetin inhibited the activity of TPA-induced protein kinase C by 66 and 50%, respectively Wang et al (1996). Aqueous saffron extract Female Swiss albino mice Saffron treatment before and after DMBA application reduced papilloma formation Das et al (2004;.…”
mentioning
confidence: 99%